Fostering Sustainable Islamic Education: A Capacity Building Initiative for Pro-Environmental Pesantren - Aptiani Nur Jannah; Grace Sandra Pramesty Rachmanda (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2026)
The concept of environmentalism in Islam, often referred to as religious environmentalism or green Islam, is gaining popularity in response to growing environmental concerns. The concept of green Islam is rooted in the idea that Islam is inevitably linked with ethical and spiritual responsibility to address complex environmental challenges. According to the National Waste Management Information System (2025), unmanaged waste makes up 66% of all waste, and over 60% of Indonesia’s major rivers are categorized as moderately to severely contaminated (Ministry of Environment and Forestry, 2024). Within the context of Indonesia, Muslim communities are increasingly impacted by environmental crises. Therefore, the Center for the Study of Islam and Society (PPIM) UIN Jakarta is conducting capacity-building for pro environmental pesantren to promote the initiation of environmental programs in pesantren. This capacity-building focuses on improving management, resources, and a curriculum that integrates environmental aspects, thereby enabling pesantren to actively contribute towards sustainable development and maintain the ecosystem balance in nearby areas. This activity also promotes the role of pesantren as agents of social change with emphasis on the environment.